La tenencia de la tierra en la región de La Piedad, Michoacán. Siglo XIX - Pimentel Espinoza, Miriam Araceli (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The present thesis analyzes the historical configuration that made possible the setting of La Piedad´s region in the 19th century, identifying and developing the fundamental social and agrarian circumstances that allowed his construction and consolidation. The region was raised with land ownership, as the common thread and attraction, which gives us the possibility of analyze the concepts and social processes that lead to the formation of the region, characterized by small properties. The region included La Piedad, Michoacán, part of Pénjamo, Guanajuato and Degollado, Jalisco, we developed it in three mainstays; the density of the population throughout the 19th century, the division and trading of Santa Ana Pacueco´s latifundium by the tenants in 1856 and finally, the proximity of the owners of ranches around in La Piedad.

La presente tesis analiza la configuración histórica que hizo posible la formación de la región de La Piedad en el siglo XIX, identificando y desarrollando las coyunturas sociales y agrarias fundamentales que permitieron su construcción y consolidación. La región se planteó teniendo como hilo conductor y de atracción la tenencia de la tierra, lo que nos proporciona la posibilidad de analizar los conceptos y los procesos sociales que llevaron a la formación de dicha región, caracterizada por la pequeña propiedad. La región comprendió La Piedad, Michoacán, parte de Pénjamo, Guanajuato y Degollado, Jalisco, y la cimentamos en tres pilares: la densidad poblacional durante todo el siglo XIX, la división y compraventa del latifundio de Santa Ana Pacueco por parte de los arrendatarios en 1856 y por último el avecinamiento de los propietarios de los ranchos a los alrededores de La Piedad.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16337; info:eu-repo/classification/cti/4; IIH-D-2023-0254; Tenencia de la tierra; Comunidades; Ranchos